Numerical study of the deflection of a light beam passing through the magnetosphere of a magnetar under the influence of gravity and nonlinear electrodynamics of vacuum - Beissen, N.; Toktarbay, S.; Alimkulova, M.; Yernazarov, T.; Shynggyskhan, N. (Recent Contributions to Physics, 2025)
This study presents a numerical investigation of the influence of nonlinear vacuum electrodynamics and gravitational effects on the propagation of electromagnetic radiation through a magnetar’s magnetosphere. Based on the Born–Infeld model, an effective metric is constructed, and the corresponding geodesic equations are numerically solved using the Runge–Kutta method. The results reveal light trajectory bending and wavefront deformation around the magnetar. The wavefront is shown to deform from a circular to an elliptical shape, accompanied by anisotropy in the distribution of energy density. It is found that near the magnetar’s surface, the deflection angle exceeds 86°, and the energy density increases by a factor of 1.83. These findings provide insights into the behavior of light propagation under extreme field conditions and are significant for future astrophysical observations and the development of theoretical models.